...sigh..another problem how shall I prove the following? $$ {\cot A\over1- \tan A} + {\tan A \over 1- \cot A} = 1 + \tan A + \cot A$$

so what now? the following's what I've done: $$\cot A - \cot^2 A + \tan A- \tan^2 A \over 2 - \tan A - \cot A$$

  • 1
    $\begingroup$ try to avoid LCM for the denominator before simplification. Observe that $1-\cot A=-\frac{1-\tan A}{\tan A}$ $\endgroup$ – lab bhattacharjee May 8 '13 at 15:12

Let $\tan A=a\implies \cot A=\frac1a$

So, the problem reduces to

$$\frac{\frac1a}{1-a}+\frac a{1-\frac1a}=\frac1{a(1-a)}+\frac{a^2}{a-1}$$ $$=\frac1{a(1-a)}-\frac{a^2}{1-a}=\frac{1-a^3}{a(1-a)}=\frac{1+a+a^2}a=a+\frac1a+1$$


$$\frac{\tan A}{1-\cot A}=\frac{\tan^2A}{\tan A-1} (\text{ multiplying the numerator & the denominator by }\tan A) $$

$$\implies \frac{\tan A}{1-\cot A}=-\frac{\tan^2A}{1-\tan A}$$

$$\text{So,} {\cot A\over1- \tan A} + {\tan A \over 1- \cot A}={\cot A\over1- \tan A} -\frac{\tan^2A}{1-\tan A}=\frac{\cot A-\tan^2A}{1-\tan A}=\frac{1-\tan^3A}{\tan A(1-\tan A)} (\text{ multiplying the numerator & the denominator by }\tan A) $$

$$=\frac{1+\tan A+\tan^2A}{\tan A}\text{ (assuming }1-\tan A\ne0)$$

$$=\cot A+1+\tan A$$

  • $\begingroup$ +1 for the first method that makes the problem clearer. (Also, don't you mean "assuming $\tan A ≠ 0$"?) $\endgroup$ – Mohamad Ali Baydoun May 8 '13 at 15:21
  • $\begingroup$ @Magtheridon96, no. Have you seen that I've cancelled $1-\tan A?$ $\endgroup$ – lab bhattacharjee May 8 '13 at 15:24
  • $\begingroup$ Oh I see. That assumption was referring to the previous step :v $\endgroup$ – Mohamad Ali Baydoun May 8 '13 at 15:25
  • $\begingroup$ How do you get $1 + tanA + tan^2A$ from $1-tan^3A$ in the last 2 steps? $\endgroup$ – Ghost May 8 '13 at 15:50
  • $\begingroup$ @Ghost, $a^3-b^3=(a-b)(a^2+ab+b^2)$ $\endgroup$ – lab bhattacharjee May 8 '13 at 15:51

$$ \begin{align} \frac{\cot A}{1-\tan A}+\frac{\tan A}{1-\cot A}&=\frac{\cos A\cot A - \sin A \tan A}{\cos A-\sin A} \\\\&=\frac{\frac{\cos^2 A}{\sin A} - \frac{\sin^2 A}{\cos A}}{\cos A-\sin A} \\\\&=\frac{\cos^3 A - \sin^3 A}{(\cos A \sin A)(\cos A-\sin A)} \\\\&=\frac{\cos^2 A + \sin^2 A + \sin A\cos A}{\cos A \sin A} \\\\&=1+\cot A+\tan A \end{align} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.